Rosetting in Plasmodium vivax: a cytoadhesion phenotype associated with anaemia. - Alejandro Marín-Menéndez; Azucena Bardají; Flor E Martínez-Espinosa; Camila Bôtto-Menezes; Marcus V Lacerda; Jon Ortiz; Pau Cisteró; Mireia Piqueras; Ingrid Felger; Ivo Müeller; Jaume Ordi; Hernando del Portillo; et al. (Public Library of Science (PLoS), 2013)
BACKGROUND: Plasmodium vivax can potentially lead to life-threatening episodes but the mechanisms underlying severe disease remain poorly defined. Cytoadhesion of infected erythrocytes may contribute to P. vivax sequestration and organ injury although its physiological impact is still unknown. Here, we aimed to describe clinically-relevant cytoadhesive phenotypes of P. vivax isolates. METHODOLOGY/PRINCIPAL FINDINGS: Rosetting and adhesion to CSA, CD36, ICAM1, placental and brain cryosections were determined in P. vivax peripheral isolates from 12 pregnant women, 24 non-pregnant women and 23 men from Manaus (Brazil). P. falciparum co-infection was excluded by PCR and P. vivax isolates were genotyped by assessing the size polymorphism of microsatellites ms2, ms20 and msp1F3 through capillary electrophoresis of PCR products. P. vivax monoinfection was confirmed by PCR in 59 isolates, with 50 (85%) of them being single-clone infections. One P. vivax haplotype was more frequently found among pregnant women (33%) than in non-pregnant women (0%) and men (4%; p=0.010). Rosetting was observed in 64% of the isolates, adhesion to CSA in 15%, to ICAM1 in 12% and to placental cryosections in 9%, being similar among pregnant and non-pregnant groups. Intensity of rosetting was higher among anaemic individuals compared to non-anaemic (p=0.010) and decreased with increasing haematocrit (p=0.033) and haemoglobin levels (p=0.015). CONCLUSIONS/SIGNIFICANCE: P. vivax peripheral isolates from pregnant women do not exhibit a prominent adhesion to CSA, although other parasite phenotypes still unknown may increase the propagation of certain P. vivax clones observed among pregnant hosts. Rosetting is a frequent cytoadhesive phenotype in P. vivax infections that may contribute to the development of anaemia.